2008
DOI: 10.1097/mpg.0b013e318162c43c
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Fiber Mixture versus Lactulose in the Treatment of Childhood Constipation: A Double‐blind Randomized Controlled Trial

Abstract: A fluid fiber mixture and lactulose give comparable results in the treatment of childhood constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
0
60
0
6
Order By: Relevance
“…No RCTs on the effects of physical movement, multidisciplinary treatment, or alternative medicine (acupuncture, homeopathy, mind-body therapy, musculoskeletal manipulations such as osteopathic and chiropractic manipulations, or spiritual therapies such as yoga) for children with constipation were found. All studies were hospital-based; 3 were conducted in a general pediatric department 14,18,19 and 6 were conducted in a pediatric gastroenterology department. [11][12][13][15][16][17] The studies were highly diverse with regard to the participants, interventions, and outcome measures; therefore, a meta-analysis of all included studies could not be performed.…”
Section: Study Selection and Methodologic Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…No RCTs on the effects of physical movement, multidisciplinary treatment, or alternative medicine (acupuncture, homeopathy, mind-body therapy, musculoskeletal manipulations such as osteopathic and chiropractic manipulations, or spiritual therapies such as yoga) for children with constipation were found. All studies were hospital-based; 3 were conducted in a general pediatric department 14,18,19 and 6 were conducted in a pediatric gastroenterology department. [11][12][13][15][16][17] The studies were highly diverse with regard to the participants, interventions, and outcome measures; therefore, a meta-analysis of all included studies could not be performed.…”
Section: Study Selection and Methodologic Quality Assessmentmentioning
confidence: 99%
“…14 The study used an adequate randomization procedure, but no information on blinding of the outcome assessor was provided, no intention-to-treat analysis was performed, and the dropout rate was high and not equally distributed. Polyethylene glycol (macrogol 3350) was added if no clinical improvement was observed after 3 weeks.…”
Section: Fiber Versus Lactulosementioning
confidence: 99%
“…The necessity of step-up medication during the treatment period was comparable (P=0.996). Authors concluded that the fluid fibre mixture and lactulose gave comparable results in the treatment of childhood constipation 4 .…”
Section: Dietary Fibre and Childhood Constipationmentioning
confidence: 99%
“…Using a standardized bowel diary, parents recorded defaecation frequency during the treatment period. In addition, incontinence frequency, stool consistency, presence of abdominal pain and flatulence, necessity for step-up medication, and dry weight of faeces were recorded 4 . Of the 135 participants, 65 were randomized to treatment with fibre mixture and 70 to treatment with lactulose.…”
Section: Dietary Fibre and Childhood Constipationmentioning
confidence: 99%
See 1 more Smart Citation